2015
DOI: 10.1139/er-2014-0043
|View full text |Cite
|
Sign up to set email alerts
|

Improving the phytoextraction capacity of plants to scavenge metal(loid)-contaminated sites

Abstract: Plants are able to extract metal(loid) contaminants from the soil or water through their roots and translocate them to harvestable aerial shoots. Of late, this plant potential has been used as a phytotechnology, termed as phytoextraction, for cleaning contaminated sites, and this process has successfully removed elements like As, Cd, Cu, Ni, and Pb, among others. Exploring plants with high metal-accumulation capacity, as well as engineering new hyperaccumulators, is a need of the hour. It is assumed that hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 295 publications
1
23
0
Order By: Relevance
“…Metallothioneins (MTs) and MT-like proteins have been found in various plant species including C. esculenta. These proteins favor the transport of metals from roots to shoots (Iqbal et al, 2015). Several studies demonstrated the metal tolerance and phytoextraction efficiency of arum plant to various heavy metals such as Cd, Pb and Zn (Kashem et al, 2008;Kim et al, 2011;Kashem et al, 2013;Chayapan et al, 2015a;2015b;Madera-Parra et al, 2015;Islam et al, 2016a;2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Metallothioneins (MTs) and MT-like proteins have been found in various plant species including C. esculenta. These proteins favor the transport of metals from roots to shoots (Iqbal et al, 2015). Several studies demonstrated the metal tolerance and phytoextraction efficiency of arum plant to various heavy metals such as Cd, Pb and Zn (Kashem et al, 2008;Kim et al, 2011;Kashem et al, 2013;Chayapan et al, 2015a;2015b;Madera-Parra et al, 2015;Islam et al, 2016a;2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Given that heavy metals are persistent and non-degradable, their contamination of soil is irreversible and leads to a decline in soil fertility as well as in crop yield and quality (Luo et al, 2015). Heavy metals accumulated in plants and animals can enter the food chain and subsequently harm human health (Iqbal et al, 2015). Thus, the remediation of heavy metal-contaminated soil has long been a challenge and a popular research focus.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium has negative effects on photosynthetic pigments (Parmer et al, 2013), electron transport chain in photosynthesis, and alter membrane structure due to phospholipids degradation in cell membrane (Dhir et al, 2004). Metals accumulate in different plant species such as mustard (Brassica campestris L.) , sunflower (Helianthus annuus L.) (Iqbal et al, 2015; Abd-Allah et al, 2015), soybean (Glycine max L.) (Abdo et al, 2012), cucumber (Cucumis sativus L.) (Sun et al, 2015) and exert health hazard effects on animals by entering in the food chain ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to devise strategies for new genotypes of plants with high metal accumulation and toxicity tolerance (Iqbal et al, 2015). Exogenous application of plant growth regulators (PGRs) can increase growth rate and yield of crops under both control and stress conditions (Perveen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%